Islamic Creative Savings and Student Economic Well-Being: Evidence from Ma'had Tahfidh Al-Amien Prenduan Islamic Boarding School - Afdhalul Izzat (Universitas Al-Amien Prenduan Sumenep, 2025)
Studies on santri savings in Islamic boarding schools are generally still understood as administrative activities and basic financial education, so that their role as an instrument for improving the welfare of santri has not been empirically studied. This study aims to analyse the implementation of the Creative Savings Programme Based on Islamic Boarding Schools as an instrument for improving the welfare of students at the Ma'had Tahfidh Al-Amien Prenduan Islamic Boarding School, with a focus on the implementation mechanism and its economic implications for students. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis, then analysed using thematic analysis with source triangulation. The results show that creative savings not only function as a means of storing funds, but also play a role in shaping students' financial management patterns, increasing their ability to meet educational needs, and strengthening their economic independence within the pesantren. The novelty of this study lies in the positioning of creative savings as an instrument of santri welfare based on pesantren institutions, which expands the study of pesantren finance from a normative approach to contextual empirical analysis.